Occlusal contact patterns – Population-based data - Hützen, Daniel; Proff, Peter; Gedrange, Tomas; Biffar, Reiner; Bernhard, Olaf; Kocher, Thomas; Kordaß, Bernd (Annals of anatomy, 2007)
The reconstruction of functionally appropriate contacts between antagonistic teeth substantially determines the quality of prosthetic-restorative work. In a population-based sample comprising 2597 subjects, static occlusal contacts were registered and analysed using the GEDAS (Greifswald Digital Analyzing System), which digitally represents the contact point situation by means of silicone bite impressions. The number of contacting teeth is approximately equal on the left- and right-hand side amounting to 8.3 on the left and 8.4 on the right. Furthermore, it was shown that 39% of the maxillary bridge pontics and 33% of the mandibular bridge units are not in contact. Antagonistic contacts are missing in 41% of the maxillary and 39% of the mandibular removable denture teeth. These results show that the fabrication of fixed dentures, particularly in bridge pontics, and the inspection of removable dentures needs to be done with more care to this detail.